Determinants of Digital Zakat Adoption Among Muslim Millennials in Indonesia - Nisa Nurazizah; Rahmad Hakim; Sri Cahyaning Umi Salama; Ririn Noviyanti (Universitas Islam Negeri Ar-Raniry, 2026)
The increasing adoption of online donation platforms has transformed the collection and distribution of zakat, particularly among younger Muslim generations who are closely connected to digital technology. This study examines the factors influencing Muslim millennials’ decisions to distribute zakat through the “Kitabisa.com” platform in Indonesia. Specifically, it analyzes the roles of perceived ease of use, perceived usefulness, attitude toward use, behavioral intention to use, brand awareness, and zakat literacy in shaping decisions to utilize digital zakat platforms. The study employs a quantitative approach based on the Technology Acceptance Model (TAM), integrated with brand awareness and zakat literacy variables. Data were collected from 130 Muslim millennials in Indonesia using accidental sampling, and the analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The findings indicate that perceived ease of use significantly influences perceived usefulness but does not have a significant effect on attitude toward use. Brand awareness and zakat literacy significantly influence the decision to use the platform. Perceived usefulness significantly affects both attitude toward use and behavioral intention to use, while attitude toward use also significantly influences behavioral intention. Furthermore, behavioral intention has a significant effect on the final decision to distribute zakat through the platform. These findings highlight the importance of strengthening digital literacy, enhancing platform usability, building public trust, and expanding brand visibility to encourage wider participation in digital zakat distribution among Muslim millennials in Indonesia. ABSTRAK - Determinan Adopsi Zakat Digital pada Muslim Milenial di Indonesia. Peningkatan penggunaan platform donasi daring telah membawa perubahan signifikan dalam mekanisme pengumpulan dan pendistribusian zakat, terutama di kalangan generasi milenial Muslim yang lekat dengan perkembangan teknologi digital. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi keputusan milenial Muslim dalam menyalurkan zakat melalui platform